PENGARUH KAMARISASI, PENCAHAYAAN, SUHU DAN KELEMBABAN TERHADAP KEJADIAN TUBERKULOSIS PARU DI KABUPATEN MAROS, SULAWESI SELATAN - Yermi Yermi; Musdalifah Syamsul; Aminah Aminah (UNM Environmental Journals, 2022)
Tuberculosis (TB) is an infectious infectious disease caused by Mycobacterium tuberculosis and most often manifests in the lungs called pulmonary tuberculosis. Mycobacterium is transmitted via airborne droplets, so that a person with pulmonary tuberculosis is a source of transmission of pulmonary TB to the surrounding population. The purpose of this study was to determine the effect of the density of room conditions, lighting, temperature and humidity on the incidence of pulmonary tuberculosis in the working area of the Turikale Health Center, Turikale District, Maros Regency. This study uses a descriptive design that describes the factors that influence the incidence of pulmonary tuberculosis. The number of samples of 33 houses with positive pulmonary tuberculosis was determined by purposive sampling. The results showed that there was an influence between the density of room conditions and lighting on the incidence of pulmonary tuberculosis. There is no effect between temperature and humidity on the incidence of pulmonary tuberculosis. Suggestions for families and the home community should have enough space or rooms, especially for pulmonary tuberculosis patients to make a special room to reduce the risk of transmission to other residents of the house.